Absolute absorption cross section of 2-EHN in IR region. (June 2022) - Zins, E-L.; Guinet, M.; Rodriguez, D.; Payan, S.
Highlights: 2-EHN absorption crossections are retrieved within the 850 and 3000 cm −1 range. DFT calculations were used as guidance for vibrational attributions, and several isomers were identified. Chemometrics multivariate linear regression (MLR) was propose a model for the estimation of 2-EHN partial pressure. The adsorption/desorption equilibrium on the cell walls were in situ probed and estimated to be close to 52.% Abstract: This paper presents the first determination of the absolute absorption cross section of 2-EHN from 850 to 3000 cm −1 . The domain of application of our measurement and its accuracy are discussed. DFT calculations were used for band attributions and the identification of the different isomers existing at room temperature. The cross section measurements were used to study the adsorption/desorption processes of the gas that can occur on stainless steel cell walls and the evolution of this equilibrium when introducing 1 atm. of dry air. We also discuss the error made by neglecting those effects in terms of quantitative chemistry and air-broadening measurement.